2018
DOI: 10.12681/mms.15546
|View full text |Cite
|
Sign up to set email alerts
|

Seamounts as hot-spots of large pelagic aggregations

Abstract: The distribution of four top predators in the Tyrrhenian Sea, a sub-basin of the Mediterranean Sea, was investigated by means of random forest regression considering depth, distance from the coast, seafloor slope, and distance from seamounts as habitat descriptors on a 2x2-nautical mile regular grid. RF results are processed to estimate variable importance and model performance. Random forest architecture reached optimal sensitivity and specificity, thus providing a consistent support tool for identifying suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Importantly, our work aligns with previous observations that pelagic hotspots are associated with prominent topographic features at local scales (Worm et al, 2003;Fontes et al, 2014;Vassallo et al, 2018). It also complements a growing body of research documenting the Timor Sea as a conspicuous and globally significant epicenter of biodiversity (Tittensor et al, 2010;Moore et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, our work aligns with previous observations that pelagic hotspots are associated with prominent topographic features at local scales (Worm et al, 2003;Fontes et al, 2014;Vassallo et al, 2018). It also complements a growing body of research documenting the Timor Sea as a conspicuous and globally significant epicenter of biodiversity (Tittensor et al, 2010;Moore et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, midwater filter feeders play an important role in the downward fluxes of carbon, potentially enhancing benthic growth and, in turn, attracting a large array of predators (Carrassón & Cartes, 2002). Mesopelagic euphausiacean swarms, benthic crustaceans, and cephalopods additionally promote the attractiveness of seamounts to top predators (Fiori et al, 2016), as confirmed by the localization of cetacean hot spots corresponding to the Janua Seamount and the area including the Genoa canyon system and the two study areas (Carugati et al, 2019; Fiori et al, 2016; Fossa et al, 2015; Moulins, Rosso, Ballardini, & Würtz, 2008; Vassallo et al, 2018; Würtz, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…This has been primarily related to the synergistic actions of numerous environmental factors, mainly linked to the turbulent hydrodynamic conditions and the high planktonic productivity recorded around the summits. Such conditions generally enhance the abundance of habitat‐forming benthic filter feeders (Clark et al, 2010; Consalvey et al, 2010; Genin, Dayton, Lonsdale, & Spiess, 1986; McClain, 2007; Pitcher et al, 2008) as well as the occurrence of numerous pelagic predators (Fiori, Paoli, Alessi, Mandich, & Vassallo, 2016; Morato, Hoyle, Allain, & Nicol, 2010; Vassallo et al, 2018; Worm, Lotze, & Myers, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Indiscriminate trawling practices have also resulted in substantial alterations in benthic community composition in this region with many VME indicator species now largely absent from these areas (De la Torriente Diez et al, 2022; Grinyó et al, 2020; Pierdomenico et al, 2018). Seamounts in this region have also been shown to serve focal roles for a diverse range of threatened top predators that are vulnerable to capture in trawl nets, and so these features deserve increased attention in future marine spatial planning discussions (Bo et al, 2021; Vassallo et al, 2018). Seamounts located in the Mediterranean Sea remain largely unexplored, despite their proximity to land and research efforts need to be prioritised for these understudied areas, which experience intensive trawling activity (Bo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%